Mid‐ to Late Holocene Contraction of the Intertropical Convergence Zone Over Northeastern South America. Issue 4 (26th April 2021) - Chiessi, C. M.; Mulitza, S.; Taniguchi, N. K.; Prange, M.; Campos, M. C.; Häggi, C.; Schefuß, E.; Pinho, T. M. L.; Frederichs, T.; Portilho‐Ramos, R. C.; Sousa, S. H. M.; Crivellari, S.; et al.
Abstract: Modern precipitation over northeastern (NE) South America is strongly controlled by the seasonal meridional migration of the Intertropical Convergence Zone (ITCZ). Ample evidence from the Northern Hemisphere suggests a mid‐ to late Holocene southward migration of the ITCZ. Such a shift would be expected to increase precipitation over semi‐arid northern NE Brazil (Southern Hemisphere). However, the most robust precipitation record from northern NE Brazil shows a drying trend throughout the Holocene. Here, we address this issue presenting a high‐temporal resolution reconstruction of precipitation over northern NE Brazil based on data from a marine sediment core, together with analyses of mid‐ and late Holocene simulations performed with the fully coupled climate model FGOALS‐s2. Both, our data and the climate model simulations show a decrease in precipitation over northern NE Brazil from the mid‐ to the late Holocene. The model outputs further indicate a latitudinal contraction of the seasonal migration range of the ITCZ that, together with an intensification of the regional Walker circulation, were responsible for the mid‐ to late Holocene changes in precipitation over NE South America. Our results reconcile apparently conflicting precipitation records and climate mechanisms used to explain changes in precipitation over NE South America. Plain Language Summary: The tropical rainbelt impacts food and water security for 1 billion people. Knowing its dynamics is of utmost importance. The suggestion of a southward migration of the tropical rainbelt through the Holocene (last 11, 700 years) has influenced paleoclimatology for two decades. However, most of the available evidence supporting this suggestion comes from tropical Northern Hemisphere precipitation reconstructions like northernmost South America. They systematically show a decrease in precipitation through the Holocene. In the tropical Southern Hemisphere like northeastern Brazil, at the opposite side of the tropical rainbelt, precipitation reconstructions are, however, rare. We reconstructed mid‐ to late Holocene (last 5, 200 years) changes in precipitation over northeastern Brazil (tropical Southern Hemisphere), where modern precipitation is associated with the southern border of the tropical rainbelt. We analyzed three independent indicators of changes in precipitation recorded in marine sediments collected off northeastern Brazil. All indicators suggest a decrease in precipitation over northeastern Brazil from the mid‐ to the late Holocene. Together with climate model simulations, our results indicate a latitudinal contraction of the tropical rainbelt. A Holocene contraction of the rainbelt, in contrast to a southward migration, reconciles apparently conflicting precipitation reconstructions and provides valuable insights into the dynamics of the tropical rainbelt. Key Points: Precipitation over northern northeastern Brazil decreased from the mid‐ to the late Holocene The meridional migration range of the Intertropical Convergence Zone contracted from the mid‐ to the late Holocene Together with the intensification of the regional Walker circulation, our results reconcile previously conflicting records